Foreign direct investments in India, focus on Finnish and Swedish joint ventures - Ylitorvi, Anne Hillevi (My University, 2011)
The purpose of the thesis was to analyze the economic, political and cultural environment of India and to clarify the strategic motives for international joint venture formation (IJV) and the influence of partner selection, management control, trust and other factors into IJV performance. Also by performing an empirical study the same aspects were examined in a sample of two Finnish and two Swedish companies operating in India and as well to clarify whether there are similarities or differences in their behaviour.
Keywords: International joint venture; motives; performance; India; Finland; Sweden; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|